(untitled) (Journal of Misan Researches, 2025)
The present research aims to identify the effect of the “Your Questions and Answers” ​​and “Learning Cell” strategies on the achievement of middle school students in the subject of literature and texts. The researcher chose an experimental design with partial control (for the two experimental groups and the control group) with a post-test for achievement. The research sample is all middle schools for boys located in Misan Governorate for the academic year (2021-2022 AD). She also chose the research sample from middle school students, specifically fourth-grade middle school students in Misan Governorate, which amounted to (81) students, to be a field for implementing the research experiment. The students of the three research groups were statistically rewarded by adopting the appropriate statistical methods for the research. The researcher prepared an achievement test consisting of (40) multiple-choice paragraphs, according to the six levels of the cognitive field. Its validity was confirmed and it was presented to a group of experts and arbitrators for reliability. The researcher adopted the split-half method; The difficulty level of the paragraphs, the discrimination coefficient, and the effectiveness of the wrong alternatives were calculated. At the end of the experiment, which lasted for a full semester, which is the first semester of the academic year (2021-2022 AD), and in light of the data, the results showed that the students of the two experimental research groups outperformed the control group. In light of the results, the researcher proposed a number of recommendations, including adopting the strategies of “Your Questions and My Answers” ​​and “The Learning Cell” in teaching as one of the strategies that contribute to achieving the goals of teaching the subject of literature and texts, as well as the proposals, including preparing a comparative study between the strategies of “Your Questions and My Answers” ​​and “The Learning Cell” and modern teaching methods derived from active learning to know the difference between them.